Gluten exacerbates IgA nephropathy in humanized mice through gliadin–CD89 interaction - Papista, Christina; Lechner, Sebastian; Ben Mkaddem, Sanae; LeStang, Marie-Bénédicte; Abbad, Lilia; Bex-Coudrat, Julie; Pillebout, Evangéline; Chemouny, Jonathan M.; Jablonski, Mathieu; Flamant, Martin; Daugas, Eric; Vrtovsnik, François; et al. (Kidney international, 2015)
IgA1 complexes containing deglycosylated IgA1, IgG autoantibodies, and a soluble form of the IgA receptor (sCD89), are hallmarks of IgA nephropathy (IgAN). Food antigens, notably gluten, are associated with increased mucosal response and IgAN onset, but their implication in the pathology remains unknown. Here, an IgAN mouse model expressing human IgA1 and CD89 was used to examine the role of gluten in IgAN. Mice were given a gluten-free diet for three generations to produce gluten sensitivity, and then challenged for 30 days with a gluten diet. A gluten-free diet resulted in a decrease of mesangial IgA1 deposits, transferrin 1 receptor, and transglutaminase 2 expression, as well as hematuria. Mice on a gluten-free diet lacked IgA1-sCD89 complexes in serum and kidney eluates. Disease severity depended on gluten and CD89, as shown by reappearance of IgAN features in mice on a gluten diet and by direct binding of the gluten-subcomponent gliadin to sCD89. A gluten diet exacerbated intestinal IgA1 secretion, inflammation, and villous atrophy, and increased serum IgA1 anti-gliadin antibodies, which correlated with proteinuria in mice and patients. Moreover, early treatment of humanized mice with a gluten-free diet prevented mesangial IgA1 deposits and hematuria. Thus, gliadin–CD89 interaction may aggravate IgAN development through induction of IgA1–sCD89 complex formation and a mucosal immune response. Hence, early-stage treatment with a gluten-free diet could be beneficial to prevent disease.